A high tap density perovskite NaTaO3 nanocrystal anode driven by pseudocapacitive conversion/intercalation hybrid mechanisms for advanced Li-ion/dual-ion storage. Issue 9 (4th February 2020) - Yan, Tong; Ding, Rui; Ying, Danfeng; Huang, Yongfa; Huang, Yuxi; Tan, Caini; Sun, Xiujuan; Gao, Ping; Liu, Enhui
Abstract : A high tap density perovskite NaTaO3 nanocrystal anode powers advanced Li-ion/dual-ion storage with pseudocapacitive conversion/intercalation hybrid mechanisms. Abstract : A high tap density perovskite NaTaO3 (denoted as NTO) nanocrystal anode has been introduced for high-performance Li-ion capacitors (LICs), Li-ion batteries (LIBs) and Li-based dual-ion batteries (Li-DIBs), demonstrating the pseudocapacitive conversion/intercalation hybrid mechanisms for Li-ion storage. Both the facile kinetics and high stability of the NTO anode contribute to the excellent behavior of Li-ion/dual-ion storage in a wide temperature range.